Development of an agility test for badminton players and assessment of its validity, reliability, and specificity - de França Bahia Loureiro Júnior, L.; Barbosa de Freitas, P. (World Badminton Federation, 2016)
Agility is one of most important physical capacities for sport performance. However, in most sports fast whole-body motion is preceded by the selection of "where to run". Hence, sports successful performance depends not only on the time spent to move the body but also on the athlete`s ability to quickly and effectively determine the direction he/she should run. Some testing protocols have been created to evaluate agility in sports taking into consideration perceptual aspects, but they present some methodological issues (e.g., use of expensive devices, limited in field application). Also, to our knowledge there is no specific agility test for badminton players. Therefore, the aims of this research were (1) to develop an agility test that simultaneously assesses perception and motor capacity, (2) to examine the test`s concurrent and construct validity, and its test-retest reliability, and (3) to evaluate the specificity of this test to badminton players.